SWOT Analysis on Drone Technology in Agriculture-A Case Study Approach - Goud, E. Ravi; Dhanalakshmi, G.; Sudhakar, M.; Chowdary, K. Raghavendra; Adinarayana, M.; Sohail, M. (International Journal of Economic Plants, 2024)
The study was conducted at Krishi Vigyan Kendra, Nandyal district, Andhra Pradesh, India during June, 2023 to March, 2024 to comprehend SWOT and determined the best entry tactics for sustainability of drone technology in agriculture by using TOWS matrix. Data was purposively collected from 120 beneficiary farmers who had used drone spraying more than twice in a single crop season under agriculture drone project. Then farmer response quantified by using IFE and EFE matrices to reveal its strengths and weaknesses along with opportunities and threats. The Internal and External factor (I-E) tool is used to summarize the information gained from drone’s external and internal environment analyses. The results found that the average for IFE and EFE score 2.50 and 2.62, respectively, which reflected that opportunities and threats are more than strength and weakness of the drone technology in agriculture. It was more effective and easy in tall and dense crops i.e. Maize, Red gram and Paddy. Less availability of spare parts, poor repair and maintenance services was founded as weaknesses of the technology. I-E Matrix concluded that, technology was obtained in cell “V”, suggested hold and maintain strategy, which indicated that drone spraying is profitable for both users and operators, but there was still scope to improve operator service centers, training facilities, and reduction of drone spraying cost, which results greater adoptability of the technology.